Transplanted Children. The migration of the characters in the rewritings of tales - Connan-Pintado, Christiane (Ondina - Ondine, 2022)
As Umberto Eco has shown, famous literary characters, and in this case story characters, become migrants who live "outside their original scores". This is the phenomenon that we propose to address in the field of contemporary children’s literature. While they come from a distant past and from the world of the "deep forest", these characters undergo the effects of a rural exodus that now situates their adventures in the urban setting. By confronting them with the social representations of a new spatio-temporal context, this transplantation can be the object of a socio-poetic study, and it even represents the most accomplished example according to the theorist of this critical approach, Alain Montandon. Indeed, the variations entailed by the diegetic transposition of tales do not fail to affect their different components: the framework of the adventure, its aesthetic representation, its narrative orientation and its ideological stakes. Without prohibiting us from invoking other tales, we will attempt to study this paradigm shift from the rewritings of two Perrault tales whose characters are children: "Le Petit Chaperon rouge" and "Le Petit Poucet", as well as those of the Grimm’s neighbouring tale, "Hänsel and Gretel". Sometimes the urban setting is justified by the adoption of the literary genre of the detective story, but the corpus gathered, mainly composed of albums, more rarely of novels and plays, reveal a certain number of constants: the choice of large metropolises, such as New York; urban modernization and its shortcomings: concentration of housing, traffic jams, pollution; the contrasts between luxury and misery; the underworld, the suburbs, the "city jungle". Revisited in this light, the tales renew the discourse on childhood, on the dangers it faces, on the hopes it still holds Keywords: tales, rewritings, urbanization, childhood, family, ecology